The moving of high emission for biomass burning in China: View from multi-year emission estimation and human-driven forces. (September 2020) - Wu, Jian; Kong, Shaofei; Wu, Fangqi; Cheng, Yi; Zheng, Shurui; Qin, Si; Liu, Xi; Yan, Qin; Zheng, Huang; Zheng, Mingming; Yan, Yingying; Liu, Dantong; et al.
Highlights: The reliable multi-year biomass burning emission variation was explored. Emission factors for some ignored biomass types was proposed. The moving of high emission for biomass burning from 2003 to 2014 was clear identified. Social-economic analysis was added to assess the high emission variation and analyze the policy implication quantitatively. Abstract: Biomass burning (BB) has significant impacts on air quality, climate and human health. In China, the BB emission has changed substantially over the past decades while the multi-year variation held high uncertainty and the driving forces have addressed little attention. Here, this research aimed to conduct a comprehensive and systematic analysis of BB variation in China and provided precise and targeted BB emission reduction suggestions. The moving of high emission for BB from 2003 to 2014 was clearly identified, by the view of reliable emission estimation and anthropogenic impacts. Multiple satellite products, field survey, time varying biomass loading data and measured emission factors were adopted to better estimating BB emission and reducing the uncertainty. Social-economic analysis was added to assess the anthropogenic impacts on high emission variation quantitatively. Results showed that the cumulative BB emissions of OC, EC, CH4, NOX, NMVOC, SO2, NH3, CO, CO2, PM2.5 and PM10 during 2003-2014 were 1.6 × 10 4, 5.64 × 10 3, 3.57 × 10 4, 1.7 × 10 4, 5.44 × 10 4, 2.96 × 10 3, 6.77 × 10 3, 6.5 × 10 5, 1.15 × 10 7, 5.26 × 10 4 and 6.04 × 10 4 Gg, respectively. Crop straw burning (in-field and domestic) in northeast China plain (NEP), north China plain (NCP), northern arid and semiarid region and loess plateau were the key sources, averagely contributed 73% for all the pollutants emission. While domestic straw burning and firewood burning in Sichuan basin (SB), Yunnan-Guizhou plateau and southern China were main contributors, averagely accounting for 70% of all the pollutants emission. On regional level, high emissions were mainly found in SB, NCP and NEP. Temporally, high emissions were mainly found in crop sowing harvesting and heating seasons. From 2003 to 2014, the BB emission for different biomass species has changed significantly in different regions. High emission has gradually moved from SB to NCP and NEP. Firewood burning and domestic straw burning emission decreased by 47% and 14% in SB, respectively. In-field straw burning emission increased by 52% and 231% in NCP and NEP respectively and domestic straw burning emission increased by 62% in NEP. Emissions from heating season have decreased while emissions in corn harvest season were continuously increased. Analysis of Environmental kuznets curve, agricultural productivity level, human burning habits, rural energy structure and local control policies revealed the internal human driving strength of the variation for BB emission. The unbalanced development of social economy and the policy bias were primary drivers of limiting the BB management. BB emission will alleviate in NCP and aggravate in NEP. For the further emission reduction, effective measures for corn sources management, straw returning and rural energy utilization should be systematically considered. This research provides a clear evidence for the multi-year variation pattern of BB emissions, which is critical for pollution prediction, air quality modeling and targeted mitigation strategies for the key regions of China.